(untitled) - Đặng, Vũ Phương Thảo (Hà Nội, 2008)
Nội dung tài liệu gồm 16 bài luyện tập, mỗi bài có các mục pronunciation, vocabulary, grammar, reading, writing
Keywords: English language,Tiếng Anh; Problems, exercises, etc,Câu hỏi, bài tập, vv